Local and Landscape Drivers of Ground Bird Flocking Behavior in Urban Parks of Buenos Aires City, Argentina - Lucas M. Leveau (Birds, 2025)
The flock formation of bird species is a crucial behavioral process that enables them to colonize urban areas. However, the factors influencing the structure and composition of ground-feeding bird flocks have not yet been analyzed. This study aimed to relate flock characteristics, including size, number, species richness, and composition, to local and landscape factors in the urban parks of Buenos Aires City, Argentina. Surveys of flocks were conducted in 16 parks during the breeding season, covering both mono-specific and mixed-species flocks. Flock numbers were positively correlated with tree, lawn, and bare ground cover but negatively associated with raptor presence in the parks. Flock species richness declined with increased noise and pedestrian traffic but rose in parks where raptors were present. The composition of species in flocks was linked to tree cover, noise, and the presence of raptors. While the Rock Dove (Columba livia) and the Rufous-bellied Thrush (Turdus rufiventris) were more abundant in parks with greater tree cover, the Eared Dove (Zenaida auriculata) and the Monk Parakeet (Myiopsitta monachus) showed increased abundance in more open parks. Zenaida auriculata and Columba livia experienced a decline in abundance in parks where raptors were present. Our findings indicate that resource availability and predation risk are crucial factors shaping flock formation in urban parks.